The non-disciplinary contradictory record, in the Educational Administration of Catalonia - Berengueras Pont, Mercè; Vera Mur, José María (Avances en Supervisión Educativa, 2018)
The communication analyzes the current conceptual and normative framework of the non-disciplinary contradictory file, focusing it as an element of the process of evaluating the teaching competence of interim teaching staff in Catalonia, when a result of negative evaluation is considered or when insufficient performance is detected that there is no inhibition or that there is a clear lack of capacity to perform professionally the place of work assigned to prevent effectively fulfilling the assigned functions. Its difference is also analyzed with the disciplinary files, both in its conceptual and procedural framework and, the consequences of these in its terminal phase. The intervention of the Education Inspectorate throughout its development process, from its inception and proposal to the end, preferably in the procedural aspects, is also subject to analysis in this communication, as well as the role played by the directors of the centers. The positive aspects and also those susceptible to improvement, derived from its implementation, complete the communication.